Near-field strong coupling of single quantum dots - Groβ, H.; Hamm, J.M.; Tufarelli, Tommaso; Hess, O.; Hecht, B. (American Association for the Advancement of Science, 2018)
Strong coupling and resultant mixing of light and matter states is an important asset for future quantum technologies. Here we demonstrate deterministic room-temperature strong coupling of a mesoscopic colloidal quantum dot to a plasmonic nano resonator at the apex of a scanning probe. Enormous Rabi splittings of up to 110meV are accomplished by nanometer– precise positioning of the quantum dot with respect to the nanoresonator probe. We find that in addition to a small mode volume of the nanoresonator, collective coherent coupling of quantum dot band-edge states and near-field proximity interaction are vital ingredients for the realization of near-field strong coupling of mesoscopic quantum dots. The broadband nature of the interaction paves the road towards ultrafast coherent manipulation of the coupled quantum dot-plasmon system at ambient conditions.